The relative importance of performance factors in Korean archery - Kim, H. -B.; Kim, S. -H.; So, W. Y. (The Journal of Strength and Conditioning Research, 2015)
This study explored the factors affecting archery performance by calculating their relative importance in Korean archery. This study used the Delphi technique and the analytic hierarchy process (AHP). After reviewing the literature and collecting data on performance factors in archery, the importance of factors affecting archery performance was calculated by holding meetings with experts (20 archery experts) and conducting confirmatory factor analysis (463 archers) and the AHP (36 archery experts). Performance factors were divided into mental, skill, and fitness categories. Fitness factors affecting performance included "drawing a bow without an arrow," "lower-body weight training," and "upper-body weight training." Skill factors affecting performance included "extending by maintaining left and right shoulder balance during aiming," "shooting skill over a regular clicker time," "maintaining pace and direction at release," and "drawing skill by maintaining left and right shoulder balance." Mental factors affecting performance were "confidence," "concentration," "emotion control," and "positive thinking." "Confidence" was identified as the most important factor among the 11 subfactors. The performance factors identified in this study and their relative importance in determining successful performance can be used in training for optimal archery performance worldwide